Normalizing Illegality: Multimodal Manipulation in Indonesian Online Gambling Advertisements - Mochammad Rizki Juanda; Kurniawan Suryatama (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
Online gambling in Indonesia remains a widespread yet illegal activity, with promotional strategies evolving to evade detection and legal sanctions. This study investigates the persuasive and deceptive techniques used in online gambling advertisements by analyzing both textual and visual elements through the framework of Systemic Functional Linguistics (SFL). The dataset consists of 34 headline-style advertisements accompanied by images, all extracted from news feed platforms. The findings reveal a notable shift from traditional promotional formats—often featuring authoritative figures—to the use of ordinary individuals such as students, food vendors, and local workers. This transition reflects a socio-economic targeting strategy, aimed particularly at middle- to low-income groups who may be more vulnerable to gambling appeals. The visual and linguistic construction of sudden wealth, casual success, and relatable personas serves to normalize gambling behavior and obscure its illegality. These patterns suggest a deliberate effort to embed gambling discourse within everyday contexts, enhancing its persuasive power. The study recommends increased public awareness campaigns, improved digital literacy education, and stronger regulatory oversight to help identify and counteract these multimodal tactics in online gambling promotion.